The Effect of CSR Disclosure, Family Ownership, And Profitability on Tax Aggresiveness with Company Size as Moderating Variable - Hari Dhoho Tampubolon (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Tax aggressiveness is an action to minimize taxable income through tax planning both legally and illegally in order to reduce the tax burden. This research is a type of quantitative research with the aim of finding out the influence of CSR Disclosure, Family Ownership, Profitability and Company Size on Tax Aggresiveness. The population used in this research is mining sector companies listed on the Indonesian Stock Exchange (BEI)in 2019-2023. The type and data used in this research is secondary data obtained from the official IDX website and the website of each company. The sampling method used was the purposive sampling method. The analytical method used is multiple regression with the SPSS application. The result of this research show that the CSR disclosure variable has a negative effect and profitability has a positive effect on tax aggressiveness. Meanwhile, the family ownership variable has no effect on tax aggressiveness. This research also succeeded in proving that company size can strengthen the negative relationship between CSR disclosure variables and tax aggressiveness